The Mediating Role of Job Satisfaction on the Influence of Person-Job Fit and Work-Life Balance on Organizational Commitment among Working Students - Rahayu Safrianita; Yuni Kasmawati (Bulletin of Pedagogical Research, 2025)
The phenomenon of low organizational commitment among working students who tend to engage in job hopping is a crucial issue in higher education, particularly in employee class programs. Based on pre-research results, 56% of working students at Budi Luhur University planned to leave their jobs, indicating low organizational commitment. This condition is influenced by the lack of person-job fit and work-life balance, which can decrease job satisfaction and ultimately weaken organizational commitment. This research aims to analyze the influence of person-job fit and work-life balance on organizational commitment with job satisfaction as a mediating variable among working students. This research uses a quantitative method with a causal approach. The sampling technique uses purposive sampling. The sample in this research was 215 active working students from the Employee Class at Budi Luhur University. The instruments used to collect data are questionnaires measured using a 5-point Likert scale. The data analysis technique used is Structural Equation Modeling (SEM) with the Partial Least Square (PLS) approach using SmartPLS 4.0 software. The results show that person-job fit has a positive and significant effect on organizational commitment (p-value = 0.006). Work-life balance does not have a significant direct effect on organizational commitment (p-value = 0.628). Person-job fit and work-life balance each have a positive and significant effect on job satisfaction (p-value = 0.000). Job satisfaction has a positive and significant effect on organizational commitment (p-value = 0.000). Job satisfaction partially mediates the influence of person-job fit on organizational commitment and fully mediates the influence of work-life balance on organizational commitment. Thus, it can be concluded that work-life balance can only increase organizational commitment if it is first able to enhance job satisfaction